(untitled) (Journal of Engineering, 2024)
In the present work, the finite element method has been used to investigate the behavior of reinforced concrete slabs subjected to dynamic loads. Eight-node Serendipity degenerated elements have been employed. This element is based on isoperimetric principles with modifications, which relax excessive constraints. The modifications include reduced order integration to overcome the shear locking.A layered approach is adopted to discretize the concrete through the thickness. Both an elastic-perfectly plastic and strain hardening plasticity approaches have been employed to model the compressive behavior of the concrete. A tensile strength criterion is used to initiation of crack and a smeared fixed crack approach is used to model the behavior of the cracked concrete. Five models are used to consider the effect of tension stiffening in the cracked concrete.Implicit Newmark with corrector-predictor algorithm is employed for time integration of the equation of motion.Several examples are analyzed using the proposed model. The numerical results showed good agreement with other sources.